Perancangan Sistem Pendaftaran Santri Baru Berbasis Web Dengan Menggunakan Metode Waterfall Pada Pondok Pesantren Tahfidz Qur’an Darussalam - Vina Sumsari; RR. Rina Antasari; Eriene Dheanda Absharina; Anggari Ayu Prahartiningsyah; Harisdianto (LKP KARYA PRIMA KURSUS, 2026)
The development of information technology has encouraged educational institutions to utilize digital systems to support administrative processes, including new student enrollment. At Pondok Pesantren Ma’had Tahfidz Qur’an Darussalam, the enrollment process was previously carried out manually, which was considered inefficient and caused difficulties for prospective students, especially those coming from outside the region. The manual process also had the potential to cause delays in data processing and irregularities in recording applicant data. Therefore, an information system is needed to support a more structured and accessible student enrollment process. This research focuses on designing a web-based new student enrollment system at Pondok Pesantren Ma’had Tahfidz Qur’an Darussalam. The system development method used is the Waterfall method, which includes the stages of requirements analysis, system design, and implementation. The analysis stage was conducted to examine system requirements based on the enrollment mechanism that was previously carried out manually. The design stage focused on developing the system workflow and designing the student enrollment form. Furthermore, the system was implemented using the PHP programming language and a MySQL database. The resulting system supports the online new student enrollment process by providing features for student account registration, structured enrollment data entry through comprehensive question items, and applicant data management by the administrator. With the implementation of this system, the student data collection process becomes more organized and assists the boarding school in managing enrollment data more effectively and efficiently.